Mixed-mode ensemble asteroseismology of low-luminosity Kepler red giants - Kuszlewicz, James S.; Hon, Marc; Huber, Daniel (The astrophysical journal, 2023)
We present measurements of the dipole mode asymptotic period spacing (ΔΠ1), the coupling factor between the p- and g-modes (q), the g-mode phase offset (ϵ g ), and the mixed-mode frequency rotational splitting (δ ν rot) for 1074 low-luminosity red giants from the Kepler mission. Using oscillation mode frequencies extracted from each star, we apply Bayesian optimization to estimate ΔΠ1 from the power spectrum of the stretched-period spectrum and to perform the subsequent forward modeling of the mixed-mode frequencies. With our measurements, we show that the mode coupling factor q shows significant anticorrelation with both the stellar mass and metallicity, and can reveal highly metal-poor stars. We present the evolution of ϵ g up the lower giant branch up to before the luminosity bump, and find no significant trends in ϵ g or δ ν rot with the stellar mass and metallicity in our sample. Additionally, we identify six new red giants showing anomalous distortions in their g-mode pattern. Our data products, code, and results are provided in a public repository.
Gesehen am 06.12.2024